Kolaborasi Artificial Intelligence dalam Peningkatan Kebutuhan Bisnis di Era Society 5.0 - Muhammad Ghazi Mubarokah; Aji Wibawa (Universitas Ngeri Malang, 2022)
Society 5.0 is people who can solve problems and challenges by using various technology-oriented innovations born in the 4.0 era, in this era where a large amount of information is accumulated from sensors in physical space in virtual space. An example is artificial intelligence. In this study, library research methods or also called library research were used. Literary study is a series of activities related to methods of collecting literature, reading, and processing research materials. The keyword search results found several academic journals and books related to the research question. There are a total of 10 resources in the source library, including: 4 scientific articles, 2 books, 2 essays, 2 online articles, all available online. This research resulted in several conclusions that AI collaboration with Society 5.0 has many advantages and disadvantages because Society 5.0 itself is an era where users do not compete with AI, but instead support technology and human resources that are mutually sustainable. Society 5.0 adalah orang yang mampu memecahkan masalah dan tantangan dengan berbagai inovasi berbasis teknologi yang lahir di era 4.0 dimana sensor di ruang fisik mengumpulkan informasi dalam jumlah besar di ruang virtual. Contohnya adalah kecerdasan buatan. Penelitian ini menggunakan metode riset kepustakaan atau library research. Penelitian kepustakaan merupakan kegiatan yang berkaitan dengan metode pengumpulan literatur. Di bawah istilah pencarian ini Anda akan menemukan beberapa jurnal ilmiah dan buku tentang pertanyaan penelitian. Pustaka sumber daya memiliki total 10 sumber daya termasuk: 4 artikel ilmiah, 2 buku, 2 esai, 2 artikel online, semuanya tersedia online. Kajian ini menghasilkan beberapa kesimpulan bahwa kerjasama AI dengan Society 5.0 memiliki banyak keuntungan dan kerugian, karena Society 5.0 sendiri merupakan era dimana pengguna tidak bersaing dengan AI tetapi dengan dukungan teknologi berkelanjutan dan sumber daya manusia saling bersaing.